Positive electrode lithium supplement material and preparation method and application thereof

By using gas-producing lithium-containing cores and particle size gradient design, the problem that lithium-adding materials can only achieve single lithium supplementation in the existing technology is solved, and the uninterrupted lithium supplementation of the battery during multiple cycles is achieved, which improves the battery's cycle stability and long-term use ability.

CN115312887BActive Publication Date: 2025-04-18SHENZHEN DYNANONIC INNOVAZONE NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210574394.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-25
Publication Date
2025-04-18
Estimated Expiration
2042-05-25

AI Technical Summary

Technical Problem

The existing lithium supplement materials can only achieve a single lithium supplement effect and cannot continuously supplement the battery's active lithium loss during the circulation process, resulting in insufficient battery circulation stability and long-term use capability.

Method used

The lithium-containing core that does not produce gas is used as the positive electrode lithium supplement material. Through the design of the cladding layer and the utilization of particle size gradient, lithium ions are slowly released during multiple cycles, achieving uninterrupted lithium supplementation.

Benefits of technology

It improves the cycle stability and long-term use capability of the battery, maintains the abundant lithium ions in the battery system, and ensures the characteristics of high capacity and long cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003661490680000191
    Figure BDA0003661490680000191
  • Figure BDA0003661490680000192
    Figure BDA0003661490680000192
  • Figure BDA0003661490680000201
    Figure BDA0003661490680000201
Patent Text Reader

Abstract

The present application relates to the technical field of lithium-ion batteries, and in particular to a positive electrode lithium replenishing material and its preparation method and application. The positive electrode lithium replenishing material provided includes a non-gas-producing lithium-containing core and a coating layer coated on the surface of the lithium-containing core; wherein the lithium-containing core includes a first lithium-containing core particle and a second lithium-containing core particle, and the particle size of the first lithium-containing core particle is smaller than the particle size of the second lithium-containing core particle; due to the uniform mixing of the two particles of different sizes, the lithium ions are gradually and continuously released during the charging process of multiple cycles, so that the positive electrode lithium replenishing material has a sustained release performance, can continuously replenish the lost active lithium, achieve uninterrupted lithium replenishment, and improve the cycle stability of the battery, thereby maintaining the abundance of active lithium ions in the battery system, and can ensure that the battery material has the characteristics of high capacity and long cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium-ion batteries, and in particular relates to a positive electrode lithium supplement material and a preparation method and application thereof. Background Art

[0002] During the first charge of a lithium-ion battery, a solid electrolyte membrane (SEI membrane) will be generated on the electrode surface due to the decomposition of the electrolyte, causing the lithium in the positive electrode material to turn into lithium carbonate or lithium alkoxide, ester salt, etc., thereby causing an irreversible reduction in active lithium, reducing the initial efficiency of the negative electrode material, and reducing the reversible capacity, that is, reducing the battery energy density.

[0003] In order to solve the problem of low initial efficiency of the negative electrode, the existing main methods include lithium replenishment of positive and negative electrode materials and lithium replenishment of pole pieces. Lithium replenishment of pole pieces usually requires the use of highly active lithium powder or lithium foil, which not only has high requirements on equipment and working environment, but also has high risks and uneven lithium replenishment. Lithium replenishment at the material end is less dangerous and can be better applied to existing battery production lines and is accepted by more people.

[0004] Most lithium replenishing additives can replenish the irreversible lithium ions consumed by the formation of SEI film in the battery after the first charge and delithiation, thereby maintaining the abundance of active lithium ions in the battery system. However, since gas will be generated in the process of lithium replenishment, the gas generated by the delithiation of the lithium replenishing material and the gas generated by the decomposition of the electrolyte during the formation of the lithium-ion battery must be extracted at one time before the battery is packaged, and during the charging and discharging process after the battery is packaged, the lithium replenishing material can no longer produce gas, that is, it must be completely delithiated in the formation stage to avoid battery bulging; and the first complete delithiation means that it only forms a single lithium replenishment effect on the battery, and can only achieve a single lithium replenishment effect. It is impossible to continuously replenish the active lithium loss generated in the subsequent cycle process of the battery, which is not conducive to achieving the cycle stability of the battery, nor is it conducive to the long-term use of the battery. Summary of the invention

[0005] The purpose of the present application is to provide a positive electrode lithium replenishing material and a preparation method and application thereof, aiming to solve the problem that the lithium replenishing material in the prior art can only achieve a single lithium replenishing effect and cannot continuously replenish lithium in the subsequent cycle process of the battery.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application provides a positive electrode lithium replenishing material, wherein the positive electrode lithium replenishing additive includes a non-gas-producing lithium-containing core and a coating layer coated on the surface of the lithium-containing core; wherein the lithium-containing core includes a first lithium-containing core particle and a second lithium-containing core particle, and the particle size of the first lithium-containing core particle is smaller than the particle size of the second lithium-containing core particle.

[0008] In a second aspect, the present application provides a method for preparing a positive electrode lithium supplement material, comprising the following steps:

[0009] Providing a first lithium-containing core particle and a second lithium-containing core particle, and a transition metal salt;

[0010] Pre-treating the first lithium-containing core particle and the second lithium-containing core particle to obtain a lithium-containing core;

[0011] The lithium-containing core and the transition metal salt are subjected to a first mixing treatment to prepare a coating layer;

[0012] An inert atmosphere is provided, and the coating layer is crystallized to obtain a positive electrode lithium supplement material.

[0013] In a third aspect, the present application provides a positive electrode plate, which comprises a positive electrode collector and a positive electrode active material layer located on the positive electrode collector, wherein the positive electrode active material layer comprises a positive electrode active material, a binder, a conductive agent and a positive electrode lithium replenishing material, wherein the positive electrode lithium replenishing material is selected from a positive electrode lithium replenishing material or is prepared by a method for preparing a positive electrode lithium replenishing material.

[0014] In a fourth aspect, the present application provides a secondary battery, wherein the secondary battery comprises a positive electrode plate.

[0015] In the positive electrode lithium replenishment material provided in the first aspect of the present application, the provided lithium-containing core is a non-gas-producing lithium-containing core, which will not produce gas from beginning to end during the lithium replenishment process, and it is not necessary to completely remove lithium in the formation stage. In addition, the provided lithium-containing core includes first lithium-containing core particles and second lithium-containing core particles with different particle sizes. Since the two particles with different particle sizes are evenly mixed, when charging for the first time, a portion of the lithium ions of the first lithium-containing core particles with a smaller particle size are released first to achieve the lithium replenishment effect. In the subsequent cycle process, the lithium ions of the first lithium-containing core particles and the second lithium-containing core particles mixed between the second lithium-containing core particles with a larger particle size are gradually released in batches, so that the lithium ions are slowly and continuously released in the subsequent charging process of many cycles, so that the positive electrode lithium replenishment material has a sustained release performance, can continuously replenish the lost active lithium, achieve uninterrupted lithium replenishment, and improve the cycle stability of the battery, thereby maintaining the abundance of lithium ions in the battery system, and can ensure that the battery material has the characteristics of high capacity and long cycle.

[0016] The second aspect of the present application provides a method for preparing a positive electrode lithium replenishing material. In the preparation method, a first lithium-containing core particle and a second lithium-containing core particle are pretreated to obtain a uniform mixture of two lithium-containing cores with different particle sizes, and the mixture is treated with a transition metal salt to form a coating layer, and then a crystallization treatment is performed to transform the material of the coating layer from an irregular form to a crystalline state. The obtained positive electrode lithium replenishing material not only realizes the sustained release of lithium ions due to the presence of two lithium-containing cores with different particle sizes, but also the ion channels formed by the prepared lithium-containing core and the coating layer are beneficial to improving the ion conductivity. The formation of a crystalline coating layer is also beneficial to forming a dense structure, which can effectively isolate water vapor and carbon dioxide, so that the positive electrode lithium replenishing material has stable properties and lithium ion sustained release characteristics, and can continuously replenish active lithium for the battery, thereby improving the performance of the battery.

[0017] The third aspect of the present application provides a positive electrode plate, which includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, and the positive electrode active material layer includes the provided positive electrode lithium replenishing material. The provided positive electrode lithium replenishing material has the characteristics of sustained release of lithium ions, and can slowly and continuously release lithium ions during many cycles of charging to achieve uninterrupted lithium replenishment, thereby improving the cycle stability of the battery, so that the obtained positive electrode material has the characteristics of stable cycle performance and sufficiently high capacity.

[0018] A secondary battery provided in the fourth aspect of the present application comprises a positive electrode plate, and the positive electrode plate comprises a positive electrode lithium replenishing material, so that the obtained secondary battery can continuously replenish lithium ions, thereby improving the overall electrochemical performance of the battery and facilitating wide use. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0020] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0021] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0022] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0023] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0024] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.

[0025] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0026] A first aspect of an embodiment of the present application provides a positive electrode lithium replenishing material, wherein the positive electrode lithium replenishing additive includes a non-gas-producing lithium-containing core and a coating layer coated on the surface of the lithium-containing core; wherein the lithium-containing core includes a first lithium-containing core particle and a second lithium-containing core particle, and the particle size of the first lithium-containing core particle is smaller than the particle size of the second lithium-containing core particle.

[0027] In the positive electrode lithium replenishment material provided in the first aspect of the embodiment of the present application, the provided lithium-containing core is a non-gas-producing lithium-containing core, which will not produce gas from beginning to end during the lithium replenishment process, and it is not necessary to completely delithium in the formation stage. In addition, the provided lithium-containing core includes first lithium-containing core particles and second lithium-containing core particles with different particle sizes. Since the two particles with different particle sizes are evenly mixed, when charging for the first time, a portion of the first lithium-containing core particles with a smaller particle size are released first to achieve the lithium replenishment effect. In the subsequent cycle process, the first lithium-containing core particles and the second lithium-containing core particles mixed between the second lithium-containing core particles with a larger particle size are gradually released in batches, so that lithium ions are slowly and continuously released during the subsequent charging process of many cycles, so that the positive electrode lithium replenishment material has a sustained release performance, can continuously replenish the lost active lithium, achieve uninterrupted lithium replenishment, and improve the cycle stability of the battery, thereby maintaining the abundance of lithium ions in the battery system, and can ensure that the battery material has the characteristics of high capacity and long cycle.

[0028] In some embodiments, the positive electrode lithium supplement additive includes a non-gas-producing lithium-containing core. In order to ensure that the lithium supplement material can no longer produce gas during the charge and discharge process after the battery is packaged, and in order to ensure that the lithium supplement material can gradually and slowly release lithium ions, the lithium-containing core material used in this application is a non-gas-producing lithium-containing core. In some embodiments, the lithium-containing core includes Li x A y O z or Li w N, wherein 0<x≤6, 0<y≤3, 0<z≤4, 0<w≤5, and A is selected from Mn, Ti, Si, Al, Zr; N is selected from at least one of P, S, B, and Se. The provided lithium-containing core produces a solid product after delithiation, so no gas is generated from the beginning to the end of the reaction process, the above-mentioned negative effects will not exist, and it is not necessary to completely delithiate in the formation stage. The remaining active lithium can be slowly released in subsequent cycles, thereby improving the energy density of the battery. In some specific embodiments, the lithium-containing core includes LiMnO2, Li2S, and Li3P.

[0029] In some embodiments, the lithium-containing core includes a first lithium-containing core particle and a second lithium-containing core particle, and the particle size of the first lithium-containing core particle is smaller than that of the second lithium-containing core particle. Since the provided lithium-containing core includes the first lithium-containing core particle and the second lithium-containing core particle with different particle sizes, and since the two particles with different particle sizes are evenly mixed, when charging for the first time, a portion of the first lithium-containing core particles with a smaller particle size are first released to achieve the lithium replenishment effect, and in the subsequent cycle process, the first lithium-containing core particles and the second lithium-containing core particles mixed between the second lithium-containing core particles with a larger particle size are gradually released in batches, so that lithium ions are gradually released in the subsequent charging process of many cycles, so that the positive electrode lithium replenishment material has a sustained release performance, can continuously replenish the lost active lithium, achieve an uninterrupted lithium replenishment effect, and improve the cycle stability of the battery, thereby maintaining the abundance of lithium ions in the battery system, and can ensure that the battery material has the characteristics of high capacity and long cycle.

[0030] In some embodiments, the particle size of the first lithium-containing core particle is 100nm to 800nm; controlling the particle size of the first lithium-containing core particle to be nanometer-level can ensure that the particle size of the first lithium-containing core particle is smaller, and the mixture with the second lithium-containing core particle is more compact. At the same time, since the first lithium-containing core particle is nanometer-level, it is easy for lithium ions to escape and form an initial lithium ion release. In some specific embodiments, the particle size of the first lithium-containing core particle includes but is not limited to 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, and 800nm.

[0031] In some embodiments, the particle size of the second lithium-containing core particle is 0.5 μm to 20 μm; the particle size of the second lithium-containing core particle is controlled to be micron-level, and the particle size of the second lithium-containing core particle is ensured to be larger than the particle size of the first lithium-containing core particle, which can ensure that the lithium-containing core with a larger particle size is slowly released during the subsequent cycle, and gradually released during the subsequent multiple cycles of charging, so as to achieve the effect of slowly replenishing lithium. In some specific embodiments, the particle size of the second lithium-containing core particle includes but is not limited to 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm.

[0032] In some embodiments, the total mass of the lithium-containing core is 100%, and the mass percentage of the first lithium-containing core particles is 5% to 30%. The content of the first lithium-containing core particles is controlled to be relatively small, so as to ensure that the release amount of the first lithium-containing core particles is moderate during the first few charging cycles, which can ensure that the lithium ion content released in the first charge is relatively large, and the subsequent slow release of lithium ions can be ensured. If the amount of the first lithium-containing core particles added is too much, the subsequent release amount of lithium ions will be relatively low, which is not conducive to the subsequent lithium supplementation effect. In some specific embodiments, the total mass of the lithium-containing core is 100%, and the mass percentage of the first lithium-containing core particles includes but is not limited to 5%, 10%, 15%, 20%, 25%, and 30%.

[0033] In some embodiments, the total mass of the lithium-containing core is 100%, and the mass percentage of the second lithium-containing core particles is 70% to 95%. The content of the second lithium-containing core particles is controlled to be relatively high to ensure that the release of lithium ions is sufficient during subsequent cycles, and the activity lost each time is fully replenished. Under the control of voltage, an appropriate amount of lithium ions can be released during each cycle, so that the lithium ions are gradually released to achieve the effect of lithium replenishment. In some specific embodiments, the total mass of the lithium-containing core is 100%, and the mass percentage of the second lithium-containing core particles includes but is not limited to 70%, 75%, 80%, 85%, 90%, and 95%.

[0034] In some embodiments, the mass percentage of the positive electrode lithium supplement material is 100%, and the mass percentage of the lithium-containing core is 65% to 90%. Controlling the mass percentage of the lithium-containing core is more conducive to ensuring multiple slow releases of lithium ions.

[0035] In some embodiments, the positive electrode lithium supplement additive includes a coating layer coated on the surface of the lithium-containing core, wherein the material of the coating layer includes a transition metal salt, wherein the transition metal salt includes at least one of a titanium salt, a vanadium salt, and a zirconium salt. Since the ionic conductivity of the titanium salt, the vanadium salt, and the zirconium salt is relatively high, they can form ion channels with the particles on the surface of the lithium-containing core, which is beneficial to improving the ionic conductivity, making the speed of lithium ions controllable during the entire delithiation process, and combining the thickness and the ratio of lithium-containing cores of different particle sizes to achieve a slow release state, and the formation of a crystalline coating layer is also beneficial to forming a dense structure, which can effectively isolate water vapor and carbon dioxide, so that the positive electrode lithium supplement material has stable properties, has the characteristics of lithium ion slow release, can continuously replenish active lithium for the battery, and improve the performance of the battery.

[0036] In some embodiments, the coating layer forms a "transition metal-A" lithium ion slow-release channel or a "transition metal-N" lithium ion slow-release channel on the surface of the lithium-containing core. The formed lithium ion slow-release channel is conducive to controlling the lithium ion release rate to be slow, ensuring that the lithium ions can be slowly released, and the formed interface properties are more stable, the dense structure is more compact, and it can effectively isolate water vapor and carbon dioxide, so that the properties of the positive electrode lithium supplement material are stable, and it plays a role in protecting the core.

[0037] In some embodiments, the thickness of the coating layer is 5nm to 150nm; if the coating layer is too thick, it is not conducive to the escape of lithium ions, and because it occupies mass but cannot provide lithium ions, it will reduce the gram capacity of the entire lithium supplement material, affecting the lithium supplement effect; if the coating layer is too thin, it is impossible to form a film layer with strong density, affecting the stability of the lithium-containing core. In some specific embodiments, the thickness of the coating layer is selected from 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm, 8.5nm, 9nm, 9.5nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm.

[0038] In some embodiments, the positive electrode lithium supplement material further comprises: an outer shell layer coated on the surface of the coating layer; wherein the material of the outer shell layer comprises a carbon material. Providing a carbon outer shell layer is beneficial to improving the electronic conductivity of the positive electrode lithium supplement material, and is more beneficial to improving the conductive performance of the material.

[0039] In some embodiments, the thickness of the outer shell is 5nm to 150nm. If the outer shell is too thick, it is not conducive to the escape of lithium ions, affecting the lithium supplementation effect; if the outer shell is too thin, it is not conducive to improving the overall electronic conductivity of the lithium supplementation material. In some specific embodiments, the thickness of the outer shell is selected from 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm, 8.5nm, 9nm, 9.5nm, 10nm, 10.5nm, 11nm, 11.5nm, 12nm, 12.5nm, 13nm, 13.5nm, 14nm, 14.5nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm.

[0040] Correspondingly, the provided positive electrode lithium supplement material is prepared by the following positive electrode lithium supplement material preparation method.

[0041] A second aspect of the present application provides a method for preparing a positive electrode lithium supplement material, comprising the following steps:

[0042] S01. Providing a first lithium-containing core particle and a second lithium-containing core particle, a transition metal salt;

[0043] S02. The first lithium-containing core particles and the second lithium-containing core particles are pretreated to obtain a lithium-containing core;

[0044] S03. The lithium-containing core and the transition metal salt are first mixed to prepare a coating layer;

[0045] S04. Provide an inert atmosphere and crystallize the coating layer to obtain a positive electrode lithium supplement material.

[0046] The second aspect of the embodiment of the present application provides a method for preparing a positive electrode lithium replenishing material. In the preparation method, a first lithium-containing core particle and a second lithium-containing core particle are pretreated to obtain a uniform mixture of two lithium-containing cores with different particle sizes, and the mixture is treated with a transition metal salt to form a coating layer, and then a crystallization treatment is performed to transform the material of the coating layer from an irregular shape to a crystalline state. The obtained positive electrode lithium replenishing material not only realizes the sustained release of lithium ions due to the presence of two lithium-containing cores with different particle sizes, but also the ion channels formed by the prepared lithium-containing core and the coating layer are beneficial to improving the ion conductivity. The formation of a crystalline coating layer is also beneficial to forming a dense structure, which can effectively isolate water vapor and carbon dioxide, so that the positive electrode lithium replenishing material has a temperature property, has the characteristics of sustained release of lithium ions, can continuously replenish active lithium for the battery, and improve the performance of the battery.

[0047] In step S01, a first lithium-containing core particle, a second lithium-containing core particle, and a transition metal salt are provided respectively according to the positive electrode lithium supplement material; wherein, the first lithium-containing core particle, the second lithium-containing core particle, and the transition metal salt are the same as those shown above, and will not be described here for the sake of space saving.

[0048] In some embodiments, the lithium-containing core can be prepared from lithium salts or lithium sheets using conventional techniques in the art.

[0049] In some embodiments, ball milling is used to obtain first lithium-containing core particles and second lithium-containing core particles with different particle sizes.

[0050] In step S02, the first lithium-containing core particles and the second lithium-containing core particles are pretreated to obtain lithium-containing core particles; the first lithium-containing core particles and the second lithium-containing core particles are mixed evenly by the pretreatment.

[0051] In step S03, the lithium-containing core and the transition metal salt are subjected to a first mixing treatment to prepare a coating layer.

[0052] In some embodiments, the lithium-containing core is first dispersed in an organic solvent to obtain a lithium-containing core dispersion, and then mixed with a transition metal.

[0053] In some embodiments, the molar ratio of the lithium-containing core to the transition metal salt is 100:2 to 15. In some specific embodiments, the molar ratio of the lithium-containing core to the transition metal salt includes but is not limited to 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14, 100:15.

[0054] In some embodiments, the first mixing treatment is performed at a temperature of 20-25° C. for 18-24 hours to react the particles on the surface of the lithium-containing core with the transition metal salt to generate a “transition metal-N” lithium ion slow-release channel or a “transition metal-A” lithium ion slow-release channel.

[0055] In step S04, an inert atmosphere is provided, and the coating layer is crystallized to obtain a positive electrode lithium supplement material.

[0056] In some embodiments, the inert atmosphere includes, but is not limited to, at least one of nitrogen, argon, neon, and helium.

[0057] In some embodiments, the crystallization temperature is 380-400° C. and the time is 3-5 hours. Through the crystallization treatment, the transition metal salt of the coating layer is transformed from a random state to a crystalline state, the structural arrangement is stable, and the formed coating layer is more dense, effectively isolating water and carbon dioxide in the air.

[0058] In some embodiments, the positive electrode lithium supplement material further includes an outer shell layer, and the preparation method of the outer shell layer includes:

[0059] A carbon material is provided, and a carbon outer shell layer is prepared on the surface of the coating layer by a solvent thermal method.

[0060] A third aspect of an embodiment of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode active material layer located on the positive electrode collector, wherein the positive electrode active material layer includes a positive electrode active material, a binder, a conductive agent and a positive electrode lithium replenishing material, wherein the positive electrode lithium replenishing material is selected from a positive electrode lithium replenishing material or is prepared by a method for preparing a positive electrode lithium replenishing material.

[0061] A third aspect of an embodiment of the present application provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer comprising a provided positive electrode lithium replenishing material, the provided positive electrode lithium replenishing material has the characteristic of sustained release of lithium ions, and can slowly and continuously release lithium ions during many cycles of charging to achieve uninterrupted lithium replenishment, thereby improving the cycle stability of the battery, so that the obtained positive electrode material has the characteristics of stable cycle performance and sufficiently high capacity.

[0062] In some embodiments, the positive electrode active material includes but is not limited to at least one of lithium iron phosphate, ternary materials, lithium cobalt oxide, and lithium manganese oxide.

[0063] In some embodiments, the mass percentage of the positive electrode lithium supplement material is 1% to 15%, with the mass of the positive electrode active material layer being 100%. Since the lithium supplement additive provides a large amount of Li, and most of the Li cannot be circulated, and since the lithium ions of the lithium supplement additive can rarely be embedded after being released, the reversible capacity that can be provided is very small. If the amount added is too much, the final reversible capacity of the material will be low, that is, the effective reversible capacity of the battery will be very low, which will have a negative effect; if the amount added is small, the lithium ions that the lithium supplement additive can provide are very limited, and it cannot effectively supplement lithium to improve the material's initial efficiency and battery energy density.

[0064] In some specific embodiments, the mass percentage of the positive electrode lithium supplement additive in the positive electrode active material layer is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%.

[0065] A fourth aspect of an embodiment of the present application provides a secondary battery, the secondary battery comprising a positive electrode plate.

[0066] A secondary battery provided in the fourth aspect of an embodiment of the present application comprises a positive electrode plate, and the positive electrode plate comprises a positive lithium replenishing material, so that the obtained secondary battery can continuously replenish lithium ions, thereby improving the overall electrochemical performance of the battery and facilitating wide use.

[0067] In some embodiments, the amount of lithium ions released during the first charging process of the secondary battery is 10%-50%.

[0068] In some embodiments, the lithium ion release amount of the secondary battery during the second charge is 5%-20%.

[0069] In some embodiments, the lithium ion release amount of the secondary battery in the first 100 cycles is 40%-80%.

[0070] In some embodiments, the lithium ion release of the secondary battery in the first 2000 cycles is 80-90%.

[0071] In some embodiments, the lithium ion release amount of the secondary battery in the first 5000 cycles is 95%-100%.

[0072] The following describes the invention in conjunction with specific embodiments.

[0073] Example A1

[0074] Positive electrode lithium supplement material and preparation method thereof

[0075] The positive electrode lithium replenishing material is Li2S@TiS2@C with sustained release characteristics, including a Li2S-containing core, a TiS2 coating layer and a carbon outer shell layer coating the core; the mass percentage of the first lithium-containing core particle of Li2S is 10%, and the mass percentage of the second lithium-containing core particle is 90%; the thickness of the coating layer and the carbon layer are 6nm and 8nm respectively.

[0076] The preparation method comprises the following steps:

[0077] Li2SO4 and an appropriate amount of PVP and citric acid are mixed and ball-milled to make them uniformly mixed and reduce the particle size, and then loaded into a corundum boat, transferred to a tube furnace and heat-treated at 800°C for 2 hours to obtain Li2S particles, and then the Li2S particles are ball-milled for 2 hours to obtain a first lithium-containing core particle with a particle size of 300 nm and a second lithium-containing core particle with a particle size of 1 μm;

[0078] The first lithium-containing core particles and the second lithium-containing core particles are uniformly mixed by premixing to obtain a lithium-containing core;

[0079] Provide a glove box, disperse the particles containing lithium core Li2S into anhydrous ethyl acetate, then add a proper amount of transition metal salt TiCl4 thereto, stir overnight at room temperature, Li2S on the surface of the particles reacts with TiCl4 to form a TiS2 coating layer and LiCl, and remove the LiCl byproduct by centrifugation with anhydrous tetrahydrofuran;

[0080] Heat treatment was performed at 400°C in an Ar atmosphere to remove the residual anhydrous ethyl acetate and crystallize TiS2 to obtain Li2S@TiS2.

[0081] The carbon coating was carried out by solvothermal method to obtain the positive electrode lithium supplement material Li2S@TiS2@C.

[0082] Example A2

[0083] Positive electrode lithium supplement material and preparation method thereof

[0084] The positive electrode lithium replenishing material is Li2S@TiS2@C with sustained release characteristics, including a Li2S-containing core, a TiS2 coating layer and a carbon outer shell layer coating the core; the mass percentage of the first lithium-containing core particles of Li2S is 15%, and the mass percentage of the second lithium-containing core particles is 85%; the thicknesses of the coating layer and the carbon layer are 6nm and 8nm, respectively.

[0085] The preparation method comprises the following steps:

[0086] Li2SO4 and an appropriate amount of PVP and citric acid are mixed and ball-milled to make them uniformly mixed and reduce the particle size, and then loaded into a corundum boat, transferred to a tube furnace and heat-treated at 800°C for 2 hours to obtain Li2S particles, and then the Li2S particles are ball-milled for 4 hours to obtain a first lithium-containing core particle with a particle size of 100 nm and a second lithium-containing core particle with a particle size of 0.5 μm;

[0087] The first lithium-containing core particles and the second lithium-containing core particles are uniformly mixed by premixing to obtain a lithium-containing core;

[0088] Provide a glove box, disperse the particles containing lithium core Li2S into anhydrous ethyl acetate, then add a proper amount of transition metal salt TiCl4 thereto, stir overnight at room temperature, Li2S on the surface of the particles reacts with TiCl4 to form a TiS2 coating layer and LiCl, and remove the LiCl byproduct by centrifugation with anhydrous tetrahydrofuran;

[0089] Heat treatment was performed at 400°C in an Ar atmosphere to remove the residual anhydrous ethyl acetate and crystallize TiS2 to obtain Li2S@TiS2.

[0090] The carbon coating was carried out by solvothermal method to obtain the positive electrode lithium supplement material Li2S@TiS2@C.

[0091] Example A3

[0092] Positive electrode lithium supplement material and preparation method thereof

[0093] The positive electrode lithium replenishing material is Li2S@TiS2@C with sustained release characteristics, including a Li2S-containing core, a TiS2 coating layer and a carbon outer shell layer coating the core; the mass percentage of the first lithium-containing core particle of Li2S is 20%, and the mass percentage of the second lithium-containing core particle is 80%; the thickness of the coating layer and the carbon layer are 6nm and 8nm respectively.

[0094] The preparation method comprises the following steps:

[0095] Li2SO4 and an appropriate amount of PVP and citric acid are mixed and ball-milled to make them uniformly mixed and reduce the particle size, and then loaded into a corundum boat, transferred to a tube furnace and heat-treated at 800°C for 2 hours to obtain Li2S particles, and then the Li2S particles are ball-milled for 1 hour to obtain a first lithium-containing core particle with a particle size of 600nm and a second lithium-containing core particle with a particle size of 3μm;

[0096] The first lithium-containing core particles and the second lithium-containing core particles are uniformly mixed by premixing to obtain a lithium-containing core;

[0097] Provide a glove box, disperse the particles containing lithium core Li2S into anhydrous ethyl acetate, then add a proper amount of transition metal salt TiCl4 thereto, stir overnight at room temperature, Li2S on the surface of the particles reacts with TiCl4 to form a TiS2 coating layer and LiCl, and remove the LiCl byproduct by centrifugation with anhydrous tetrahydrofuran;

[0098] Heat treatment was performed at 400°C in an Ar atmosphere to remove the residual anhydrous ethyl acetate and crystallize TiS2 to obtain Li2S@TiS2.

[0099] The carbon coating was carried out by solvothermal method to obtain the positive electrode lithium supplement material Li2S@TiS2@C.

[0100] Example A4

[0101] Positive electrode lithium supplement material and preparation method thereof

[0102] The positive electrode lithium replenishing material is Li2S@TiS2@C with sustained release characteristics, including a Li2S-containing core, a TiS2 coating layer and a carbon outer shell layer coating the core; the mass percentage of the first lithium-containing core particle of Li2S is 30%, and the mass percentage of the second lithium-containing core particle is 70%; the thickness of the coating layer and the carbon layer are 6nm and 8nm respectively.

[0103] The preparation method comprises the following steps:

[0104] Li2SO4 and an appropriate amount of PVP and citric acid are mixed and ball-milled to make them uniformly mixed and reduce the particle size, and then loaded into a corundum boat, transferred to a tube furnace and heat-treated at 800°C for 2 hours to obtain Li2S particles, and then the Li2S particles are ball-milled for 1 hour to obtain a first lithium-containing core particle with a particle size of 800nm ​​and a second lithium-containing core particle with a particle size of 5μm;

[0105] The first lithium-containing core particles and the second lithium-containing core particles are uniformly mixed by premixing to obtain a lithium-containing core;

[0106] Provide a glove box, disperse the particles containing lithium core Li2S into anhydrous ethyl acetate, then add a proper amount of transition metal salt TiCl4 thereto, stir overnight at room temperature, Li2S on the surface of the particles reacts with TiCl4 to form a TiS2 coating layer and LiCl, and remove the LiCl byproduct by centrifugation with anhydrous tetrahydrofuran;

[0107] Heat treatment was performed at 400°C in an Ar atmosphere to remove the residual anhydrous ethyl acetate and crystallize TiS2 to obtain Li2S@TiS2.

[0108] The carbon coating was carried out by solvothermal method to obtain the positive electrode lithium supplement material Li2S@TiS2@C.

[0109] Example A5

[0110] Positive electrode lithium supplement material and preparation method thereof

[0111] The positive electrode lithium replenishing material is Li3P@Ti3P4@C with sustained release characteristics, including a Li3P-containing core, a Ti3P4 coating layer coating the core, and a carbon outer shell layer; the mass percentage of the first lithium-containing core particles of Li3P is 15%, and the mass percentage of the second lithium-containing core particles is 85%; the thicknesses of the coating layer and the carbon layer are 7nm and 10nm, respectively.

[0112] The preparation method comprises the following steps:

[0113] In a glove box filled with argon, an appropriate amount of red phosphorus and lithium flakes were mixed in a suitable molar ratio, heated to 200°C, and the lithium metal was molten. The mixture was kept warm for 1 hour and stirred continuously to allow the two to react fully to obtain Li3P. The mixture was ball-milled for 1 hour to obtain a first lithium-containing core particle with a particle size of 400 nm and a second lithium-containing core particle with a particle size of 1.4 μm.

[0114] The first lithium-containing core particles and the second lithium-containing core particles are uniformly mixed by premixing to obtain a lithium-containing core;

[0115] Provide a glove box, disperse particles containing lithium core Li3P into anhydrous ethyl acetate, then add a proper amount of transition metal salt TiCl4 thereto, stir overnight at room temperature, Li3P on the surface of the particles reacts with TiCl4 to form a Ti3P4 coating layer and LiCl, and remove the LiCl byproduct by centrifugation with anhydrous tetrahydrofuran;

[0116] Heat treatment was performed at 400°C in an Ar atmosphere to remove the residual anhydrous ethyl acetate and crystallize Ti3P4 to obtain Li3P@Ti3P4.

[0117] The carbon coating was carried out by solvothermal method to obtain the positive electrode lithium supplement material Li2S@Ti3P4@C.

[0118] Example A6

[0119] Positive electrode lithium supplement material and preparation method thereof

[0120] The positive electrode lithium replenishing material is Li3P@Ti3P4@C with sustained release characteristics, including a Li3P-containing core, a Ti3P4 coating layer coating the core, and a carbon outer shell layer; the mass percentage of the first lithium-containing core particles of Li3P is 5%, and the mass percentage of the second lithium-containing core particles is 95%; the thicknesses of the coating layer and the carbon layer are 7nm and 10nm, respectively.

[0121] The preparation method comprises the following steps:

[0122] In a glove box filled with argon, an appropriate amount of red phosphorus and lithium flakes were mixed in a suitable molar ratio, heated to 200°C, and the lithium metal was molten. The mixture was kept warm for 1 hour and stirred continuously to allow the two to react fully to obtain Li3P. The mixture was ball-milled for 5 hours to obtain a first lithium-containing core particle with a particle size of 100 nm and a second lithium-containing core particle with a particle size of 0.5 μm.

[0123] The first lithium-containing core particles and the second lithium-containing core particles are uniformly mixed by premixing to obtain a lithium-containing core;

[0124] Provide a glove box, disperse particles containing lithium core Li3P into anhydrous ethyl acetate, then add a proper amount of transition metal salt TiCl4 thereto, stir overnight at room temperature, Li3P on the surface of the particles reacts with TiCl4 to form a Ti3P4 coating layer and LiCl, and remove the LiCl byproduct by centrifugation with anhydrous tetrahydrofuran;

[0125] Heat treatment was performed at 400°C in an Ar atmosphere to remove the residual anhydrous ethyl acetate and crystallize Ti3P4 to obtain Li3P@Ti3P4.

[0126] The carbon coating was carried out by solvothermal method to obtain the positive electrode lithium supplement material Li3P@Ti3P4@C.

[0127] Example A7

[0128] Positive electrode lithium supplement material and preparation method thereof

[0129] The positive electrode lithium replenishing material is Li3P@Ti3P4@C with sustained release characteristics, including a Li3P-containing core, a Ti3P4 coating layer coating the core, and a carbon outer shell layer; the mass percentage of the first lithium-containing core particles of Li3P is 20%, and the mass percentage of the second lithium-containing core particles is 80%; the thicknesses of the coating layer and the carbon layer are 7nm and 10nm, respectively.

[0130] The preparation method comprises the following steps:

[0131] In a glove box filled with argon, an appropriate amount of red phosphorus and lithium flakes were mixed in a suitable molar ratio, heated to 200°C, and the lithium metal was molten. The mixture was kept warm for 1 hour and stirred continuously to allow the two to react fully to obtain Li3P. The mixture was ball-milled for 1 hour to obtain a first lithium-containing core particle with a particle size of 500 nm and a second lithium-containing core particle with a particle size of 3.5 μm.

[0132] The first lithium-containing core particles and the second lithium-containing core particles are uniformly mixed by premixing to obtain a lithium-containing core;

[0133] Provide a glove box, disperse particles containing lithium core Li3P into anhydrous ethyl acetate, then add a proper amount of transition metal salt TiCl4 thereto, stir overnight at room temperature, Li3P on the surface of the particles reacts with TiCl4 to form a Ti3P4 coating layer and LiCl, and remove the LiCl byproduct by centrifugation with anhydrous tetrahydrofuran;

[0134] Heat treatment was performed at 400°C in an Ar atmosphere to remove the residual anhydrous ethyl acetate and crystallize Ti3P4 to obtain Li3P@Ti3P4.

[0135] The carbon coating was carried out by solvothermal method to obtain the positive electrode lithium supplement material Li3P@Ti3P4@C.

[0136] Example A8

[0137] Positive electrode lithium supplement material and preparation method thereof

[0138] The positive electrode lithium replenishing material is Li3P@Ti3P4@C with sustained release characteristics, including a Li3P-containing core, a Ti3P4 coating layer coating the core, and a carbon outer shell layer; the mass percentage of the first lithium-containing core particles of Li3P is 30%, and the mass percentage of the second lithium-containing core particles is 70%; the thicknesses of the coating layer and the carbon layer are 7nm and 10nm, respectively.

[0139] The preparation method comprises the following steps:

[0140] In a glove box filled with argon, an appropriate amount of red phosphorus and lithium flakes were mixed in a suitable molar ratio, heated to 200°C, and the lithium metal was molten. The mixture was kept warm for 1 hour and stirred continuously to allow the two to react fully to obtain Li3P. The mixture was ball-milled for 1 hour to obtain a first lithium-containing core particle with a particle size of 700 nm and a second lithium-containing core particle with a particle size of 4.5 μm.

[0141] The first lithium-containing core particles and the second lithium-containing core particles are uniformly mixed by premixing to obtain a lithium-containing core;

[0142] Provide a glove box, disperse particles containing lithium core Li3P into anhydrous ethyl acetate, then add a proper amount of transition metal salt TiCl4 thereto, stir overnight at room temperature, Li3P on the surface of the particles reacts with TiCl4 to form a Ti3P4 coating layer and LiCl, and remove the LiCl byproduct by centrifugation with anhydrous tetrahydrofuran;

[0143] Heat treatment was performed at 400°C in an Ar atmosphere to remove the residual anhydrous ethyl acetate and crystallize Ti3P4 to obtain Li3P@Ti3P4.

[0144] The carbon coating was carried out by solvothermal method to obtain the positive electrode lithium supplement material Li3P@Ti3P4@C.

[0145] Comparative Example A1

[0146] The Li2S particles purchased from Aladdin were not ball-milled but carbon-coated by a solvothermal method to obtain micron-sized Li2S@C. The particle size of Li2S was 1 μm, accounting for 50% of all particles, and the thickness of the carbon coating layer was 10 nm.

[0147] Comparative Example A2

[0148] A certain amount of biphenyl and lithium metal were dissolved in anhydrous dimethyltetrahydrofuran to obtain 1 mol / L of organic lithiation reagent, to which an appropriate amount of sulfur nanoparticles were added, stirred overnight, filtered and dried to obtain Li2S nanoparticles. Then, the carbon was coated by solvothermal method to obtain nanoscale Li2S@C. The particle size of Li2S is 50nm, accounting for 10% of all particles, and the thickness of the carbon coating layer is about 10nm.

[0149] Comparative Example A3

[0150] Micron-sized Li3P was purchased from the market and directly carbon-coated by a solvothermal method without any treatment to obtain micron-sized Li3P@C. The particle size of Li3P was 1.3 μm, accounting for 40% of all particles, and the thickness of the carbon coating layer was about 9 nm.

[0151] Comparative Example A4

[0152] First, 1 mol / L of organic lithiation reagent was prepared, and an appropriate amount of red phosphorus nanoparticles was added thereto, stirred overnight, filtered and dried to obtain Li3P nanoparticles. Then, carbon coating was performed using a solvothermal method to obtain nanoscale Li3P@C. The particle size of Li3P was 100nm, accounting for 15% of all particles, and the thickness of the carbon coating layer was 10nm.

[0153] Embodiment B1 to Embodiment B8

[0154] Positive electrode

[0155] The positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, a binder, a conductive agent and a positive electrode lithium replenishing material, wherein the positive electrode lithium replenishing additive is selected from the positive electrode lithium replenishing materials provided in Examples A1 to A8 respectively, and lithium iron phosphate is used as the positive electrode active material, according to (lithium replenishing material + main material): SP-Li:PVDF=95:2:3, wherein the lithium replenishing material is 3% of the weight of the main material, and N-methylpyrrolidone (NMP) is used as a solvent to mix the three materials evenly to form a slurry, and then evenly coat it on the surface of the aluminum foil, roll it to a certain thickness, and vacuum dry it at 110°C for 12 hours to form a positive electrode plate.

[0156] Comparative Example B1 to Comparative Example B4

[0157] Positive electrode

[0158] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, a binder, a conductive agent and a positive electrode lithium replenishing material, wherein the positive electrode lithium replenishing additive is selected from the positive electrode lithium replenishing materials provided in Comparative Examples A1 to Comparative Examples A4 respectively, and lithium iron phosphate is used as the positive electrode active material, according to (lithium replenishing material + main material): SP-Li:PVDF=95:2:3, wherein the lithium replenishing material is 3% of the weight of the main material, and N-methylpyrrolidone (NMP) is used as a solvent to mix the three materials evenly to form a slurry, and then evenly coat it on the surface of the aluminum foil, roll it to a certain thickness, and vacuum dry it at 110°C for 12 hours to form a positive electrode sheet.

[0159] Example C1 to Example C8

[0160] Secondary battery

[0161] The positive electrode plates and negative electrode plates, separators and electrolytes obtained in Examples B1 to B8 were assembled to obtain batteries, wherein the negative electrode plates were selected from pure lithium plates, the separators were selected from polypropylene microporous membranes, and the electrolytes were selected from 1 mol / L LiPF6 / ethylene carbonate: methyl ethyl carbonate (volume ratio) = 1:1 solution. The assembled battery model was CR2032, and the corresponding lithium plate diameter was 16.5 mm and the thickness was 0.4 mm. The positive electrode diameter was 15 mm.

[0162] Comparative Example C1 to Comparative Example C4

[0163] Secondary battery

[0164] The positive electrode plates and negative electrode plates, separators and electrolytes obtained in Comparative Examples B1 to B4 were assembled to obtain batteries, wherein the negative electrode plates were selected from pure lithium plates, the separators were selected from polypropylene microporous membranes, and the electrolytes were selected from 1 mol / L LiPF6 / ethylene carbonate: methyl ethyl carbonate (volume ratio) = 1:1 solution. The assembled battery model was CR2032, and the corresponding lithium plate diameter was 16.5 mm and the thickness was 0.4 mm. The positive electrode diameter was 15 mm.

[0165] Performance Testing

[0166] Here, the present application uses the gram capacity of the buckle test to characterize the amount of lithium ion released in a certain cycle. Due to the discharge process, a small amount of lithium ions will be re-embedded into the positive electrode lithium supplement in the lower part of the voltage window, so the amount of lithium ion released in the first n cycles is equal to the total charge capacity of the first n cycles minus the total discharge capacity of the first n cycles. The following Tables 1 and 2 give the data of the lithium ion release of the buckle assembled by these embodiments and comparative samples in some representative cycles, as shown in Tables 1 and 2.

[0167] Table 1

[0168]

[0169] Table 2

[0170]

[0171]

[0172] Among them, the Li2S-based lithium supplement contains 80% lithium-containing core (Li2S) by mass, and the corresponding theoretical specific capacity is 932mAh / g. The Li3P-based lithium supplement contains 70% lithium-containing core (Li3P) by mass, and the corresponding theoretical specific capacity is 1088mAh / g.

[0173] From Table 2, it can be seen that in Example A1-8, the amount of lithium ions released in the first 1000 cycles is continuously increasing, which means that more new lithium ions are released in each cycle. Among them, the lithium-replenishing materials with smaller particle sizes release relatively more lithium ions in the first few times, and the cumulative release ratio of lithium ions in the first 1000 cycles is also relatively high. This is because the particle size is smaller and lithium ions are easier to escape. As for the comparative examples A1 and A3, the particle size of the lithium-replenishing materials is generally larger, and the release of lithium ions is more difficult. Although they can be released slowly, the final cumulative release ratio is small, resulting in the lithium-replenishing agent being unable to fully play its role. This is not the result we want to see. The lithium-replenishing materials in comparative examples A2 and A4 have a smaller particle size, and most of the lithium ions can be released during the first charging process, and can also be released later, but the release amount is small, which does not meet the goal of sustained release.

[0174] In summary, in the positive electrode lithium replenishment material provided by the present application, the lithium-containing core provided is a non-gas-producing lithium-containing core, which will not produce gas from beginning to end during the lithium replenishment process, and it is not necessary to completely delithium in the formation stage. In addition, the provided lithium-containing core includes a first lithium-containing core particle and a second lithium-containing core particle with different particle sizes. Since the two particles with different particle sizes are evenly mixed, when charging for the first time, a portion of the lithium ions of the first lithium-containing core particles with a smaller particle size are released first to achieve the lithium replenishment effect. In the subsequent cycle process, the lithium ions of the first lithium-containing core particles and the second lithium-containing core particles mixed between the second lithium-containing core particles with a larger particle size are gradually released in batches, so that the lithium ions are slowly and continuously released in the subsequent charging process of many cycles, so that the positive electrode lithium replenishment material has a sustained release performance, can continuously replenish the lost active lithium, achieve uninterrupted lithium replenishment, and improve the cycle stability of the battery, thereby maintaining the abundance of lithium ions in the battery system, and can ensure that the battery material has the characteristics of high capacity and long cycle.

[0175] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A positive electrode lithium supplement material, characterized in that: The positive electrode lithium supplement material includes a non-gas-producing lithium-containing core and a coating layer coated on the surface of the lithium-containing core; wherein the lithium-containing core includes a first lithium-containing core particle and a second lithium-containing core particle, and the particle size of the first lithium-containing core particle is smaller than the particle size of the second lithium-containing core particle; the particle size of the first lithium-containing core particle is 100 nm to 800 nm; the particle size of the second lithium-containing core particle is 0.5 μm to 20 μm; The lithium-containing core includes Li x A y O z or Li w N, wherein 0<x≤6, 0<y≤3, 0<z≤4, 0<w≤5, and A is selected from at least one of Mn, Ti, Si, Al, and Zr; N is selected from at least one of P, S, B, and Se; The material of the coating layer includes a transition metal salt; The coating layer forms a "transition metal-A" lithium ion sustained-release channel or a "transition metal-N" lithium ion sustained-release channel on the surface of the lithium-containing core; The coating layer has a thickness of 5 nm to 150 nm.

2. The positive electrode lithium supplement material according to claim 1, characterized in that: Taking the total mass of the lithium-containing core as 100%, the mass percentage of the first lithium-containing core particles is 5%-30%, and the mass percentage of the second lithium-containing core particles is 70%-95%.

3. The positive electrode lithium supplement material according to claim 1, characterized in that: The transition metal salt includes at least one of a titanium salt, a vanadium salt and a zirconium salt.

4. The positive electrode lithium supplement material according to claim 1, characterized in that: The positive electrode lithium supplement material further includes: an outer shell layer coated on the surface of the coating layer; wherein the material of the outer shell layer includes a carbon material.

5. The positive electrode lithium supplement material according to claim 4, characterized in that: The thickness of the outer shell layer is 5 nm to 150 nm.

6. The positive electrode lithium supplement material according to claim 1, characterized in that: Taking the mass of the positive electrode lithium supplement material as 100%, the mass percentage of the lithium-containing core is 65% to 90%.

7. A method for preparing a positive electrode lithium supplement material as claimed in claim 1, characterized in that: The steps include: Providing a first lithium-containing core particle and a second lithium-containing core particle, and a transition metal salt; Pre-treating the first lithium-containing core particle and the second lithium-containing core particle to obtain a lithium-containing core; Performing a first mixing treatment on the lithium-containing core and the transition metal salt to prepare a coating layer; An inert atmosphere is provided, and the coating layer is crystallized to obtain a positive electrode lithium supplement material.

8. The method for preparing a positive electrode lithium supplement material according to claim 7, characterized in that: The temperature of the first mixing treatment is 20-25° C. and the time is 18-24 hours.

9. The method for preparing a positive electrode lithium supplement material according to claim 7, characterized in that: The crystallization treatment is performed at a temperature of 380-400° C. and for a time of 3-5 hours.

10. The method for preparing a positive electrode lithium supplement material according to claim 7, characterized in that: The molar ratio of the lithium-containing core to the transition metal salt is 100:2-15.

11. The method for preparing a positive electrode lithium supplement material according to any one of claims 7 to 10, characterized in that: The positive electrode lithium supplement material further includes an outer shell layer, and the preparation method of the outer shell layer includes: A carbon material is provided, and a carbon outer shell layer is prepared on the surface of the coating layer by a solvent thermal method.

12. A positive electrode sheet, characterized in that: The positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, a binder, a conductive agent and a positive electrode lithium replenishing material, wherein the positive electrode lithium replenishing material is selected from the positive electrode lithium replenishing material described in any one of claims 1 to 6 or is prepared by the preparation method of the positive electrode lithium replenishing material described in any one of claims 7 to 11.

13. The positive electrode sheet according to claim 12, characterized in that: Taking the mass of the positive electrode active material layer as 100%, the mass percentage of the positive electrode lithium supplement material is 1% to 15%.

14. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet as described in any one of claims 12-13.

15. The secondary battery according to claim 14, characterized in that: The amount of lithium ions released during the first charging process of the secondary battery is 10%-50%; and / or, The lithium ion release amount of the secondary battery during the second charge is 5%-20%.

16. The secondary battery according to claim 14, characterized in that: The lithium ion release amount of the secondary battery in the first 100 cycles is 40%-80%; and / or, The lithium ion release of the secondary battery in the first 2000 cycles is 80-90%; and / or, The lithium ion release of the secondary battery in the first 5000 cycles is 95%-100%.

Citation Information

Patent Citations

  • Pre-lithiation film with high lithium content and preparation method and application thereof

    CN109616601A

  • Lithium ion battery positive electrode material and preparation method and application thereof

    CN110797511A

  • Lithium titanate / lithium ion conductor / carbon composite material and preparation method and application thereof

    CN113937260A